Arbuscular Mycorrhiza Inoculum Type Influences Phosphorus Subcellular Distribution in Shoots of Wheat Grown in Acidic Soil under Sustainable Agricultural Practices - Faria, Jorge (2021)
Crop growth in acidic soils is limited by toxicity of Al and/or Mn and deficiency of phosphorus (P). Arbuscular mycorrhizal fungi (AMF) improve host water and nutrient acquisition, particularly P. When colonization is initiated from an intact extraradical mycelium (ERM), shoot P levels increase, depending on the plant species associated with ERM development (Developer). In the present study, wheat (Triticum aestivum) was grown in an acidic soil with intact ERM associated with previously grown native stress-adapted Developers. Non-mycotrophic Silene gallica (SIL) was compared with strongly mycotrophic Lolium rigidum L. (LOL) and Ornithopus compressus (ORN). After 3 weeks, wheat shoot P concentration and subcellular redistribution were analyzed via ICP-MS. ERMs established after LOL or ORN growth promoted 1.7- and 1.6-fold wheat shoot P accumulation, respectively. Shoots of wheat grown after SIL showed 40% of P in the apoplast, while after LOL or ORN, this proportion was approx. 50%. Intact ERM from mycotrophic Developers adapted to acidic soils seems to influence crop growth by increasing P uptake and managing its subcellular distribution. This knowledge is important for the development of sustainable agricultural practices in the framework of net carbon zero-emission agriculture.